The influence of landscape structure on the diversity of avifauna species in tropical urban areas of Northeastern Zimbabwe - Muderere, Trymore; Murwira, Amon; Kativu, Shakkie; Tagwireyi, Paradzayi; Chiweshe, Ngoni (Biodiversity (Nepean), 2020)
Variations in avifauna species diversity are subject to environmental factors as well as interactions with other species. We evaluated how landscape structure can influence the composition and distribution of avifauna species groups in a tropical urban landscape from the understudied region of the Harare metropolitan area in Northeastern Zimbabwe. We sampled avifauna species groups and computed patch metrics (size, shape and isolation distance) using remotely sensed data from 35 census plots representing five land use/land cover classes. Using multivariate analysis techniques, we found three habitat patch characteristics distinguishing avifauna species diversity and distribution, namely patch shape complexity (R 2 = 0.47-0.64), patch size (R 2 = 0.55-0.62) and isolation distance (R 2 = 0.73-0.78). In this study, we discuss the implications of these findings with a view to better understanding the effects of urban landscape structure on avifauna species diversity in this understudied region. In particular, contextual landscape features such as native savanna vegetation accompanied by dispersed urban development patterns could mitigate the negative impacts of urbanization on biodiversity. This study may be useful in helping to understand landscape structure-biodiversity linkages in ecosystems outside tropical savannas, as well as in other urban areas of sub-Saharan Africa. Key policy insights provide empirical information for review of town planning by-laws and align zoning proposals to habitat requirements of avifauna species, inform preparation of environmental action plans to restore degraded landscapes and ecosystems and, inform development of subdivision layout design guidelines by managing the size, shape, isolation distance and LULC composition of habitat fragments.